Analysis of Program Learning Outcome As A Result of Curriculum Evaluation In Higher Education - Wahyu Dwi Mulyono; Gde Agus Yudha Prawira Adistana; Heri Suryaman; Desi Ratna Artaningtyas; Yuli Sutoto Nugroho (IJORER : International Journal of Recent Educational Research, 2024)
Objective: One measure of achieving educational goals in higher education is the achievement of program learning outcomes (PLO). This learning achievement needs to be monitored and evaluated to develop the curriculum of the study program. This research aims to analyze the learning outcomes of undergraduate programs in building construction education. Method: This research is a type of evaluation research. The research subjects were all courses in The Undergraduate Program of Building Construction Education, Faculty of Engineering, Universitas Negeri Surabaya. Data collection techniques used documentation and observation. Data analysis used quantitative descriptive techniques. Results: The results of this study indicate that based on the evaluation of learning outcomes, several courses have yet to reach the achievement limit (below 75). Therefore, the study program needs to formulate actions that can be taken to improve this condition. The improvement plan is highly dependent on the study program's objectives, graduate users' needs, and each course's characteristics. Novelty: The novelty of this research is the differences in instruments, research subjects, time, and specific learning outcome programs in the building construction education study program.